PERLINDUNGAN HUKUM TERHADAP ANAK PELAKU PENCEMARAN NAMA BAIK DI MEDIA SOSIAL - Nurrah Tri Auliya; Hilman Nur (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the legal protection for children as perpetrators of criminal acts of defamation on social media, as well as the implementation of diversion in the settlement of juvenile cases based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Article 27A of Law Number 1 of 2024 concerning Electronic Information and Transactions. The research employs a normative juridical method with a statute approach and a conceptual approach. The legal materials used consist of primary legal materials in the form of laws and regulations, as well as secondary legal materials in the form of books and scientific journals. The data collection technique was conducted through literature study. The results of the study indicate that the criminal act of defamation on social media is regulated in Article 27A of Law Number 1 of 2024, which emphasizes the elements of intent, attacking honor or reputation, and the dissemination of electronic information to the wider public. Children who commit criminal offenses remain entitled to legal protection based on the principle of the best interests of the child. Such protection is manifested through the implementation of diversion and a restorative justice approach to protect children from the negative impacts of the formal criminal justice process. Diversion is carried out through deliberation among the perpetrator, the victim, their families, and related parties to achieve peace and the restoration of social relations. Thus, the implementation of diversion is expected to protect children's rights while simultaneously supporting the process of rehabilitation and the social reintegration of children into society.